Leaf anatomy of Cordiera sessilis (Vell.) Kuntze (Rubiaceae) (Acta Scientiarum. Biological Sciences, 2016)
A study on the leaf anatomy of Cordiera sessilis (Rubiaceae), a native medicinal shrub from Brazilian Cerrado was carried out to identify features that may be useful in species recognition. Leaves were collected, fixed and processed by usual techniques, and studied by light and electron microscopy. Quantitative analyzes of stomata and trichomes were performed. In addition to the typical anatomical characteristics of Rubiaceae leaves, two types of vascular patterns were identified in the petiole: in distal part, the vascular system is arranged cylindrically surrounded by sclerenchyma sheath and in proximal part the vascular system is arranged in U-shape coupled to sclerified cells. The micromorphological organization of leaf surface, epicuticular wax types, the petiole pattern and histochemical characteristics as the presence of druses, crystal sand and alkaloids and absence of raphides in the mesophyll, midrib and petiole are considerate representative characteristics of C. sessilis and may be useful in the species recognition.